High-Performance Green Extraction of Natural Products (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Phytochemicals from natural products are now widely used as food additives (antioxidants, pigments), food supplements, cosmetic ingredients, etc. Currently, the majority of the extraction processes implemented on an industrial scale for the production of bioactive-enriched extracts are based on solvents of petroleum origin. However, contemporary trends in green extraction techniques dictate a minimization of solvent use, low-energy processes and novel eco-friendly materials that are environmentally benign. The search for liquids and/or extraction technologies that could meet such requirements is, therefore, an intriguing concept. This book addresses the concept of recovering natural bioactive substances from plant resources, using state-of-the-art extraction technologies, with prospects in the food, cosmetic and pharmaceutical industries.